Argentina in Crisis: Superheroes in Zenitram (2010) and Kryptonita (2015) - Vinodh Venkatesh (Галактика медиа: журнал медиа исследований, 2020)
While the study of superheroes has become a comprehensive field in itself, a focus on global superheroes has only recently begun to take shape. Vinodh Venkatesh’s Capitán Latinoamérica: Superheroes in Cinema, Television, and Web Series (2020) furthers a comprehensive examination of the superhero in Latin American moving images from the late 1950s to the present day, covering contexts from Mexico to Chile. Missing from this study, however, is an examination of Argentine superheroes. The present essay fills this gap by addressing two films, Zenitram (2010) and Kryptonita (2015), that portray and critique Argentina and its relationship with neoliberalism in the 20th and 21st centuries. Both films move beyond the parameters of genre cinema by engaging salient issues extant in the cultural horizon of the country.